Histological comparison of an allograft, a xenograft and alloplastic graft as bone substitute materials - C.E. Nappe; A.B. Rezuc; A. Montecinos; F.A. Donoso; A.J. Vergara; B. Martinez (Ariesdue, 2016)
Aim An allograft, a xenograft and an alloplastic graft, associated to sinus lift or ridge preservation procedures were histologically studied to evaluate their characteristics and to obtain the percentages of bone and remaining graft particles. This may help the clinician to determine, form the histological point of view, if they are viable alternatives to the use of autograft in bone regeneration procedures. Materials and methods Twenty-five samples from 18 subjects were histologically evaluated with respect to newly formed bone and remaining graft particles percentage. Results The three studied grafting materials presented adequate osteoconduction characteristics. Differences in newly formed bone percentage were found between the allograft and the xenograft, whereas no differences were found between the allograft and the alloplastic graft or the xenograft and the alloplastic graft. There were no significant differences in the percentage of residual particles amongst the different types of graft. Conclusions All studied bone substitute materials showed good characteristics for their use in bone regeneration therapies.